2003
DOI: 10.1074/jbc.m301387200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Yeast Glutaredoxins as Glutathione S-transferases

Abstract: The yeast Saccharomyces cerevisiae contains two glutaredoxins, encoded by GRX1 and GRX2, that are required for resistance to reactive oxygen species. We recently reported that Grx1 is active as a glutathione peroxidase and can directly reduce hydroperoxides (Collinson, E. J., Wheeler, G. L., Garrido, E. O., Avery, A. M., Avery, S. V., and Grant, C. M. (2002) J. Biol. Chem. 277, 16712-16717). We now show that Grx2 is also a general hydroperoxidase, and kinetic data indicate that both enzymes have a similar patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 32 publications
2
102
1
Order By: Relevance
“…Grx1 and Grx2 Lack Peroxidase Activity-Saccharomyces cerevisiae Grx1 has been reported to be an efficient general glutathione peroxidase (37). In trypanosomes, hydroperoxide reduction is catalyzed by a cascade composed of NADPH, TR, T(SH) 2 , Tpx, and either TXNPx or Px III, which both act as tryparedoxin peroxidases (17).…”
Section: Grx1 Forms Dimeric Iron-sulfur Cluster Complexes-thementioning
confidence: 99%
See 1 more Smart Citation
“…Grx1 and Grx2 Lack Peroxidase Activity-Saccharomyces cerevisiae Grx1 has been reported to be an efficient general glutathione peroxidase (37). In trypanosomes, hydroperoxide reduction is catalyzed by a cascade composed of NADPH, TR, T(SH) 2 , Tpx, and either TXNPx or Px III, which both act as tryparedoxin peroxidases (17).…”
Section: Grx1 Forms Dimeric Iron-sulfur Cluster Complexes-thementioning
confidence: 99%
“…Alternatively, the assays contained 10 M Tpx plus 10 M Grx1 or Grx2. In analogy to the peroxidase assays described for yeast Grxs (37), the third type of assays lacked Tpx and Px III but contained 50 M Grx1 or Grx2.…”
mentioning
confidence: 99%
“…Multiple glutaredoxins are known in different organisms (8 -12), but the role of these proteins in cells and in different cell organelles is still unclear. Glutaredoxins are thought to have a primary role in defense against oxidative stress (13)(14)(15)(16)), but they have been suggested to participate in other functions, such as cellular differentiation (17), redox regulation of signal transduction (14,18) and prevention of apoptosis (15).…”
mentioning
confidence: 99%
“…Moreover, one general mechanism for cadmium detoxification, both in S. cerevisiae and mammals, is the chelation of the metal by glutathione and the subsequent compartmentalization of the GSh-metal complex (33). Many xenobiotics can react either spontaneously with the thiol moiety of GSh to form GSh-conjugates, or via glutathione S-transferases (9,18). Analysis of the genome of the studied yeast strains revealed that C. glabrata, P. pastoris and H. polymorpha have only one glutathione S-transferase orthologous either to GTT1, or to GTT3 (Table 2 and Fig.…”
Section: Sod1 Sod2 Cta1 Ctt1 Gpx1 Gpx2 Gpx3 Gtt1 Gtt2 Gtt3 Gsh1 Gsh2mentioning
confidence: 99%
“…in this respect R. graminis and especially S. pombe possess obvious advantages in comparison to other yeast strains. however, research carried out by collinson and Grant (9) showed that in S. cerevisiae two other proteins, namely Grx1p and Grx2p, have an overlapping function with that of glutathione S-transferases and are primarily responsible for intracellular glutathione S-transferase activity. thus, cells that lack glutathione S-transferases can probably also carry out the disposal of various xenobiotics and heavy metals by alternative expression of multifunctional glutaredoxins.…”
Section: Sod1 Sod2 Cta1 Ctt1 Gpx1 Gpx2 Gpx3 Gtt1 Gtt2 Gtt3 Gsh1 Gsh2mentioning
confidence: 99%